Too Hot to Handle—Quantifying Temperature Variations in the Nasal Endoscope Ocular Assembly and Light Post. Issue 2 (March 2020) - Lewis, Trevor; Levin, Marc; Sommer, Doron D.
Background: Nasal endoscopes have transformed and improved the safety of intranasal and transnasal surgery. The heat they can produce may, however, reach dangerous levels for surgeons. Studies have not previously assessed the temperature of the nasal endoscope light post/ocular assembly (LP/OA)—where the surgeon usually holds the endoscope. Objective: This study aims to understand the effect of different nasal endoscopes, light sources, and light cords on the LP/OA temperature. Methods: We measured the temperature at the LP/OA of various rigid nasal endoscopes at multiple time intervals over 30 minutes, as well as after turning off the light source and irrigating the LP/OA with 10 mL of saline. Results: The highest temperature recorded was 67.37°C at the LP/OA at 30 minutes, using a new light cord, older endoscope, and 184-hour xenon light bulb. In every trial, the temperature of the LP/OA continually increased until 30 minutes when the light source was turned off. Statistically significant ( P  < .001) temperature differences were seen in trials using the older xenon light sources. The light-emitting diode light source was significantly cooler with an older light cord regardless of the age of the scope ( P  = .003). Conclusion: Endoscope temperatures during sinus surgery may reach potentially dangerous levels at the LP/OA region. These temperatures may be sufficient to cause second-degree burns during normal usage. Factors associated with higher endoscope temperatures include longer times with the light source on and xenon light bulbs.